Scattering properties of modeled complex snowflakes and mixed‐phase particles at microwave and millimeter frequencies. Issue 16 (27th August 2014) - Ori, D.; Maestri, T.; Rizzi, R.; Cimini, D.; Montopoli, M.; Marzano, F. S.
Abstract A microphysically based algorithm (named Snow Aggregation and Melting (SAM)) that models snowflakes composed of a collection of hexagonal columns by simulating a random aggregation process is presented. SAM combines together pristine columns with multiple dimensions to derive complex aggregates constrained to size‐mass relationship obtained by data collected from in situ measurements. The model also simulates the melting processes occurring for environmental temperatures above 0°C and thus define the mixed‐phase particles structure. The single‐scattering properties of the modeled snowflakes (dry and mixed phased) are computed by using a discrete dipole approximation (DDA) algorithm which allows to model irregularly shaped targets. In case of mixed‐phased particles, realistic radiative properties are obtained by assuming snow aggregates with a 10% of melted fraction. The single‐scattering properties are compared with those calculated through Mie theory together with Maxwell‐Garnett effective medium approximation using both a homogeneous sphere and a layered‐sphere models. The results show that for large‐size parameters there are significant differences between the radiative properties calculated using complex microphysical and optical algorithms (i.e., SAM and DDA) and those obtained from simplified assumptions as the layered‐sphere models (even when the radial ice density distribution of the aggregated snowflakes is perfectly matched). Finally, some applications to quantitative precipitation estimation using radar data are presented to show how the resulting differences in the basic optical properties would propagate into radar measurable. Large discrepancies in the derivation of the equivalent water content and snowfall rate from radar measurements could be observed when large‐size parameters are accounted for.